PERLINDUNGAN HUKUM PIHAK YANG DIRUGIKAN ATAS TINDAKAN WANPRESTASI OLEH SALAH SATU PIHAK TERHADAP AKTA PERDAMAIAN - Nicky Cobitha Febriani; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The peace of deed has the power as a normal judge's decision which haspermanent legal force and against it can not be appealed or appealed. Thepurpose of writing this thesis, namely; First, the factors that lead to defaults onthe peace deed and obstacles in its settlement, Second, the legal protection of theaggrieved party by default on the peace deed and what remedies can be done.This type of research can be classified in the type of normative legalresearch. In this study the author discusses more about the principles of law,especially the principle of good faith and the principle of pacta sunt servanda inthe agreement in which the agreement referred to is a peace deed. Source of dataused, secondary data, data collection techniques in this study with literaturereview method.From the results of the research problem there are two main things thatcan be concluded. First, in this case there is a violation of the legal principles ofthe agreement and / or freedom of contract, namely the principle of pacta suntservanda and the principle of good faith. The factor of default which mostinfluences the parties is the existence of problems with the economy and theabsence of good faith from the Defendant to immediately resolve the problem ofdefault on the peace deed. The inhibiting factor in the settlement of the peace deedis also due to the lack of knowledge of the Plaintiffs on legal remedies and whatlegal protection can be taken by them as the losers. Second, the legal protection ofthe aggrieved party is still not strong enough in its implementation, the fulfillmentof this execution is carried out with the request of the winning party orally or inwriting in advance of the execution of the Court. The court makes a call againstthe Defendant who is in default to carry out the decision voluntarily (aarmaning).After the due date has not been fulfilled, it can apply for a confiscation ofcollateral. If it is still not addressed by the losing party, the Court issues adecision to make a forced decision (execution).